Adopsi Teknologi Palka Berinsulasi untuk Penanganan Ikan Segar di Pelabuhanratu, Sukabumi - Mei Dwi Erlina; Nendah Kurniasari (Universitas Gadjah Mada, 2007)
This research aimed to understand the adoption level of insulation palka for handling fresh fish, and the relationship between internal-external characteristics of fisherman with technological adoption level. The research was located in Pelabuhanratu, Sukabumi which was one of the locations for the introduction of insulation palka by Fisheries Research and Development Centre. Samples were collected by purposive sampling method, with fisherman using insulation palka to handle fresh fish as respondent. Data were analysed by descriptive analysis and non parametric (Spearman correlation) test. The result showed that fisherman in Pelabuhanratu had a high motivation to adopt insulation palka technology indicated by application of recommended technological packages. The relationship test indicated that formal education factor, family income, numbers of labours in family, reason of using insulation palka, cosmopolitan, interaction with extension agent and decision making type should be paid attention related to every effort to introduce the similar technology. Besides, external characteristics which should be paid attention were member of fisherman group, availability of infrastructure, enforcement of society leader, institution support, capital source, marketing, and culture value.